The efficacy of modified bloodless del Nido cardioplegia in isolated aortic valve replacement - Bongyeon Sohn; Jae Suk Yoo; Dong Jin Kim; Heemoon Lee (PLoS ONE, 2025)
This study aimed to evaluate the safety and efficacy of a modified, bloodless Del Nido (DN) cardioplegia solution in patients undergoing isolated aortic valve replacement (AVR). A total of 370 patients who underwent isolated AVR between 2015 and 2022 were retrospectively analyzed. Patients were categorized into two groups based on the cardioplegia solution used: the bloodless DN group (N = 180) and the histidine-tryptophan-ketoglutarate (HTK) group (N = 190). To reduce selection bias and adjust for baseline differences, inverse probability of treatment weighting analysis was performed. There was no significant difference in in-hospital mortality between the two groups (HTK vs. DN: 1.2% vs. 0.9%, P = 0.554). However, the rate of spontaneous sinus rhythm restoration without the need for defibrillation following aortic cross-clamp release was significantly higher in the DN group (40.0% vs. 75.2%, P < 0.001). Additionally, the initial postoperative lactate level (3.0 ± 2.6 mmol/L vs. 2.2 ± 1.4 mmol/L, P = 0.002), and the incidence of low cardiac output syndrome (9.4% vs. 1.7%, P < 0.001) were significantly lower in the DN group compared to the HTK group. Other postoperative morbidities did not differ significantly between the groups. The modified bloodless Del Nido cardioplegia demonstrated favorable myocardial protection and early clinical outcomes compared to HTK solution in patients undergoing isolated AVR. These findings suggest that the bloodless Del Nido technique may be a viable alternative, although further validation in larger, prospective studies is warranted.